MENINGKATKAN HASIL BELAJAR SISWA MENGGUNAKAN STRATEGI INQUIRY - Alfian Catur Syaukani; Alfian Eko Rachmawan; Sukari Sukari (Raudhah - Proud To Be Professional, 2023)
In learning, appropriate methods are needed to convey material so that students more easily understand and digest the material presented, which will basically improve student learning outcomes. Not only in the teaching and learning process, a teacher also acts as a facilitator, mediator and motivator for students. Expertise is needed in guiding, developing and managing learning activities so as to create effective and efficient teaching and learning activities. To achieve learning success, learning strategies are needed that are appropriate to the material and student characteristics. In learning science, not only mastery of knowledge, but also requires concepts and facts and principles which are a process of discovery. This study aims to find out the results of learning before and after using the inquiry strategy in science subjects with environmental change material and implementing inquiry strategies in science subjects with environmental change material. This type of research is class action research with class IV A research subjects consisting of 24 students and the instruments used are tests, observation/observation and documentation. Data collection techniques with student and teacher observation sheets. Data analysis techniques with data reduction, and data presentation. The results of this study were that during the pre-cycle of the 24 students the pre-cycle mastery level was only 41.66%. At the time of the implementation of Cycle I, it was given in the form of learning using strategies, it was known that student learning outcomes in cycle I on science subject matter had increased compared to the results of the pre test. However, the written test results have not reached completeness and are still relatively low with an average of 66.66%. And in Cycle II it increased by an average of 83.33%.